Epidermal auxin biosynthesis facilitates rhizobial infection in Lotus japonicus. (20th May 2018) - Nadzieja, Marcin; Kelly, Simon; Stougaard, Jens; Reid, Dugald
Summary: Symbiotic nitrogen fixation in legumes requires nodule organogenesis to be coordinated with infection by rhizobia. The plant hormone auxin influences symbiotic infection, but the precise timing of auxin accumulation and the genetic network governing it remain unclear. We used a Lotus japonicus optimised variant of the DII‐based auxin accumulation sensor and identified a rapid accumulation of auxin in the epidermis, specifically in the root hair cells. This auxin accumulation occurs in the infected root hairs during rhizobia invasion, while Nod factor application induces this response across a broader range of root hairs. Using the DR5 auxin responsive promoter, we demonstrate that activation of auxin signalling also occurs specifically in infected root hairs. Analysis of root hair transcriptome data identified induction of an auxin biosynthesis gene of the Tryptophan Amino‐transferase Related ( LjTar1 ) family following both bacteria inoculation and Nod factor treatment. Genetic analysis showed that both expression of the LjTar1 biosynthesis gene and the auxin response requires Nod factor perception, while common symbiotic pathway transcription factors are only partially required or act redundantly to initiate auxin accumulation. Using a chemical genetics approach, we confirmed that auxin biosynthesis has a functional role in promoting symbiotic infection events in the epidermis. Significance statement: We show that auxin rapidly accumulates in the root epidermis during the early stages of rhizobia infection. Auxin biosynthesis contributes to this accumulation and facilitates infection thread formation, and therefore represents an early symbiotically activated component of the infection pathway.